Law and Human Rights Awareness School Group: A Multi-Dimensional Study to Build a Law-Cultured Society - Aman Serah, Yenny; Rini Setiawati; Sri Ayu Septinawati; Resmaya Agnesia Mutiara Sirait (Journal of Law, Politic and Humanities, 2024)
The purpose of this study is to examine the effectiveness of the establishment and development of Law and Human Rights Aware Schools that commit to instilling legal values in their students in improving and building a law-cultured society. Through qualitative research methods and multi-dimensional studies, the results of the research show that the Law and Human Rights Awareness School coaching programme is effective in increasing students' knowledge and understanding of applicable laws and regulations. In addition, the programme also succeeded in shaping students' positive attitudes towards legal compliance and encouraging their active participation in law-related activities. A further implication is that there is a positive impact on the legal awareness of the community as a whole, where students who have participated in the Law and Human Rights Aware Schools programme become agents of change who spread legal values to their surrounding environment. Therefore, it is recommended that the Law and Human Rights Aware Schools programme be expanded and integrated more widely into the education curriculum to build a law-abiding society.